CENTRAL BANK DIGITAL CURRENCY UNDER THE STATE THEORY OF MONEY: A PRELIMINARY LEGAL ANALYSIS - Indrawati, Fransiska Ari (Journal of Central Banking Law and Institutions, 2022)
Innovations in digital payments have triggered many central banks to apprehend and consider central bank digital currency (CBDC). CBDC is believed to be the next milestone in the evolution of money because many studies have shown the significant advantages of using government-issued digital currency. However, to function as money, CBDC must fulfil the fundamental role of money, among others, contended by the state theory of money. This paper addresses the applicability of the state theory of money to CBDC as digital money, which is prefaced by the discussion on money as legal tender and the theory of sovereign power over money. After analysing these theories, this paper offers a preliminary legal analysis of CBDC, mainly from the perspective of Indonesian law. This paper concludes that the concept of CBDC as money and legal tender may fulfil the notion of money under the state theory of money and can serve as legal tender. Applying this theory to CBDC and assuming CBDC is used as legal tender, the State should create a legal framework to regulate CBDC as a valid medium of exchange and legal tender. However, it is also acknowledged that various designs of CBDC must be supported by different legal environments. Furthermore, this paper recommends the preparation of an Indonesian legal ecosystem for CBDC, consisting of a solid regulatory framework and clear legal relationships among relevant parties, that are needed to ensure the legality of the issuance, distribution and transference of CBDC once the design of CBDC is determined. Furthermore, to accommodate the use of CBDC, a thorough assessment of the relevant Indonesian laws should be undertaken relating, among other factors, to the central bank, money, currency, and technology.